Review of research progress on the theory and bearing characteristics of post-grouting for prestressed concrete pipe pile ends and sides - HOU Zhenkun; CHEN Xuanlin; TANG Mengxiong; LING Zao; DU Xidong; XU Feng; HE Shaoyang; LIANG Shihua (河南理工大学学报. 自然科学版)
Significance Post-grouting of pipe piles is an effective technique for improving the physical and mechanical properties of the pile-soil interface， playing a significant role in enhancing the frictional resistance of pipe piles and reducing settlement of the superstructure. Progress This article reviews post-grouting technology， post-grouting theory， the bearing performance of pipe piles after grouting， and the shear performance of the pile-slurry-soil interface. Furthermore， it explores the future development directions of post-grouting for pipe piles. （1） Post-grouting effectively improves the bearing capacity of small- and medium-diameter pipe piles. After grouting， the bearing capacity of pipe piles installed using the intermediate excavation method generally exceeds 4 000 kN. Additionally， the bearing capacity of static drilling and planting bamboo joint piles increases by more than 20%， while the bearing capacity of drilling and pipe piles typically exceeds 20 000 kN. （2） Existing grouting theories have facilitated advancements in grouting technology. While discrepancies exist between research findings and engineering practices， these theories provide a preliminary outline and range for slurry diffusion， offering scientific guidance for grouting design and engineering applications. （3） Most studies on the pile-slurry-soil interface utilize shear tests to analyze macroscopic behavior， focusing on the shear performance of the pile-slurry-soil interface. However， few delve into the macro- and microscopic diffusion mechanisms of grouting fluid penetrating the soil in the form of grouting roots， claws， and capillary claws. Additionally， limited attention has been given to the ion exchange processes that enhance the bond strength of the pile-slurry-soil interface. （4） Current research predominantly focuses on analyzing grouting outcomes， with insufficient exploration of grouting mechanisms. Consequently， there remains a lack of clarity regarding the flow and diffusion behaviors of grout within the soil formation. Conclusions and prospects Visual analysis of the progressive flow of grouting fluid along the pile side， quantitative characterization of the three-dimensional geometry of the grouting body， intelligent monitoring of the grouting process， and the development of novel pipe pile side grouting techniques are essential for advancing the future of pipe pile side post-grouting.